KONSTRUKSI MAKNA KRISIS IDENTITAS REMAJA PADA TOKOH KEFAS DALAM FILM SURAT UNTUK MASA MUDAKU - Nesya Amanda, Deria; Nurhaqiqi, Hanna; Mehdi Fauzi, Reza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the representation of adolescent identity crisis in the character Kefas in the Indonesian film Surat untuk Masa Mudaku (2026). Adolescents raised in orphanages are frequently portrayed through stereotypes of delinquency, whereas their behaviour is rooted in complex psychosocial experiences. This research aims to reveal how the film constructs the identity crisis of Kefas through its system of cinematic signs. The study employs a descriptive qualitative approach with Roland Barthes' semiotic analysis covering three orders of signification, namely denotation, connotation, and myth, framed conceptually by Erik Erikson's psychosocial theory of identity versus role confusion. Data were collected through documentation of selected scenes and literature study. The findings show that the film constructs the identity crisis as a gradual psychosocial process: repeated experiences of loss form the root of the crisis; role confusion manifests through aggression, rebellion, and emotional withdrawal that continue into adulthood; the presence of a caregiver figure, Simon, opens a psychosocial moratorium as a safe space for identity exploration; and the crisis is resolved through fidelity marked by self-acceptance and openness. Through these representational choices, the film shifts the audience's reading of orphanage adolescents from moral judgment and stigma toward an understanding of the psychosocial experiences underlying their behaviour.